69.5k views
1 vote
Solve the system: y = 12 + 4x y = -33 - 5x

User Luizbranco
by
4.5k points

1 Answer

2 votes

The equation system is:


\begin{gathered} y=12+4x \\ y=-33-5x \end{gathered}

So we can made the equation equal so:


\begin{gathered} 12+4x=-33-5x \\ 4x+5x=-33-12 \\ 9x=-45 \\ x=-(45)/(9) \\ x=-5 \end{gathered}

Now we can replace the value of x to find y in the first equation so:


\begin{gathered} y=12+4(-5) \\ y=12-20 \\ y=-8 \end{gathered}

so the solution is:


(-5,-8)

User Luzett
by
4.9k points